2014
DOI: 10.1352/1944-7558-119.5.405
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Knowledge in Children and Adolescents With Down Syndrome: A New Methodological Approach

Abstract: Emotion knowledge was examined in 19 youth with Down syndrome (DS) and compared to typically developing (TD) children of similar developmental levels. This project expanded upon prior research on emotion knowledge in DS by utilizing a measure that minimized the need for linguistic skills, presented emotion expressions dynamically, and included social context cues. In Study 1, participants with DS were as accurate as TD participants when judging emotions from static or dynamic expression stimuli and from facial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 64 publications
5
21
0
4
Order By: Relevance
“…The Emotional Judgment Test (Channell, Conners, & Barth, 2014), which presents brief video vignettes that vary facial and contextual cues with character emotion, has demonstrated satisfactory internal consistency with adolescents with DS, but few differences in performance have been reported between individuals with DS and nonverbal mental age-matched typically developing controls (Channell et al, 2014). Psychometric properties important for clinical trials, such as test-retest and sensitivity to change, have yet to be addressed, and the ease of administration will need to be examined.…”
Section: Resultsmentioning
confidence: 99%
“…The Emotional Judgment Test (Channell, Conners, & Barth, 2014), which presents brief video vignettes that vary facial and contextual cues with character emotion, has demonstrated satisfactory internal consistency with adolescents with DS, but few differences in performance have been reported between individuals with DS and nonverbal mental age-matched typically developing controls (Channell et al, 2014). Psychometric properties important for clinical trials, such as test-retest and sensitivity to change, have yet to be addressed, and the ease of administration will need to be examined.…”
Section: Resultsmentioning
confidence: 99%
“…The stimuli used were animations created by morphing photographs of expressive faces taken from Ekman and Friesen’s [30] set. It should be noted that this study mobilized a greater linguistic load since participants had to produce a verbal response involving emotional vocabulary, while in the study by Channell et al, [23] participants simply had to respond by pointing to a schematic face from among three faces presented and named earlier by the investigator.…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, as Channell et al [23] pointed out, the tasks used in earlier studies evaluated recognition on the basis of photographs of static facial expressions, which does not allow one to conclude that people with DS have a true deficit affecting the recognition of emotional facial expressions. Tasks that use stimuli that are closer to real-life interaction situations and richer in emotional information are necessary to continue the study of emotion recognition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, children with Down's syndrome are not significantly different from other children at emotion recognition tasks ( Pochon and Declercq 2013 ), and show similar developmental trajectories with respect to the acquisition of emotion knowledge ( Channell, Conners, and Barth 2014 ). And a recent survey of health-related quality of life revealed that although children with Down's syndrome score lower than other children on measures of motor skill and cognitive development, they score the same on measures of physical complaints and measures of positive and negative emotions, and they score better (at least in this one survey) on a measure of anxiety and depression ( van Gameren-Oosterom et al 2011 ).…”
Section: Case Two: Intellectual Disabilitymentioning
confidence: 99%